Review of tools for evaluation of leadership in market economy health care system - Sierpińska, Lidia (Nursing in the 21st Century, 2011)
Objective. The objective of the study was the presentation of tools for the evaluation of the effectiveness of leadership in health care units based on international literature.Results. The analysis conducted showed that the LPC scale (Least Preferred Co-worker) allows the assessment of the skills of an applicant to a managerial position, and his/her personality traits useful in the management of an organization. From the aspect of communication skills the SRLS scale is known (Socially Responsible Leadership Scale) for the evaluation of the efficiency of managerial staff in interpersonal contacts. According to international literature reports, the effectiveness of managerial staff leadership may be assessed by means of the LFQ 360o questionnaire (Leadership Focus Questionnaire 360o). For the evaluation of the dimension of management in the sector of services the QLP tool may be useful (Quality Leadership Profile). By means of the QLP questionnaire leader’s position in a group and his/her competences may be determined, as well as the directions of future occupational development. At all organizational levels effective and ineffective leaders, their personality traits and leadership style may be differentiated by means of the MLQ tool (Multifactor Leadership Questionnaire). The dimension of leadership in health care units may be evaluated with the use of the LBDQ questionnaire (Leader Behaviour Description Questionnaire). The effectiveness of leadership may also be assessed by means of the MBNQA scale (Malcolm Baldrige National Quality Award), while the effectiveness of leadership of nursing managerial staff and their communication skills - with the use of the MSQ scale (Management Survey Questionnaire), whereas the ALQ questionnaire (Authentic Leadership Questionnaire) is the optimum tool for the evaluation of individual elements of leader’s conduct.Conclusions. The optimum tool for the evaluation of individual elements of leader’s conduct is the ALQ questionnaire (Authentic Leadership Questionnaire).